Augmented Reality in Indonesian Language Learning: A High School Implementation Study - Heri Yani; Ridho Kurniawan; Yuannisah Aini Nasution (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to investigate the implementation of an Augmented Reality (AR)-based learning module in Indonesian language instruction at SMA Negeri 2 Rantau Utara. The goal is to improve students’ literacy skills, motivation, and classroom engagement by utilizing interactive and visually enriched learning experiences. Augmented Reality (AR) offers unique features that combine digital elements with real-world environments, making it easier for students to grasp abstract language concepts such as grammar, literary analysis, and writing structures. The research used a mixed-methods approach involving 30 high school students. Data collection instruments included pre-tests and post-tests to measure literacy improvement, student questionnaires to assess engagement and motivation, classroom observations, and interviews with teachers and students. The findings revealed that the use of the AR-based module resulted in a significant improvement in students' literacy test scores rising by 25% to 35% as well as increased classroom participation and enthusiasm. Students responded positively to the AR content, describing the lessons as more enjoyable, interactive, and easier to understand compared to traditional methods. Teachers also reported benefits, such as better student focus and improved understanding of complex material. However, challenges were identified, particularly in terms of limited access to AR-compatible devices and the need for professional training in AR integration. Despite these obstacles, the study concludes that AR has strong potential to transform Indonesian language learning by creating a more engaging, student-centered environment. This research highlights the importance of investing in educational technology infrastructure and teacher development to maximize the benefits of AR in secondary education.